Madeline’s struggle to get self-actualization in Nicola Yoon’s Everything, Everything - Fachriya Ariani Salsabila; Adeline Grace Marianne Litaay (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2023)
This research aims to discuss the issue of the struggle to achieve self-actualization in Nicola Yoon’s Everything, Everything. The research aims to analyze two points: Madeline’s struggles in search of self-actualization in Nicola Yoon’s Everything, Everything, and Madeline’s needs in Nicola Yoon’s Everything, Everything. This study applies the psychological approach and theory of human needs by Abraham Maslow. Based on the analysis, the writer reveals that despite her limitations, Madeline yearns for love, independence, and the truth about her condition. She also meets her basic needs for physiological needs and safety needs. Through her relationship with Olly and the support of her friend Carla, Madeline finds love and belonging needs, and esteem needs. Ultimately, Madeline breaks free from her confinement, embraces her true self, and pursues a life without boundaries. This novel shows that everyone has needs and struggles, but humans can find fulfillment with determination so that their self-actualization as humans is fulfilled.